The Effect of Cabbage Leaf Compresses on Breast Milk Engorgement: A Pre-Experimental Design - Rinda Lamdayani; Apriyanti Aini; Titin Apriyani; Rini Anggeriani; Yona Sari; Bedru Jemal Abafita (An Idea Health Journal, 2026)
Background: The rate of exclusive breastfeeding in Indonesia was 61.33% in 2021 and increased to 64.5% in 2022. The government has set a target of 80% for exclusive breastfeeding; however, this target has not yet been achieved. Efforts to increase this coverage include providing accurate and appropriate information regarding the benefits of exclusive breastfeeding for both mothers and infants, which can enhance public awareness of its importance. Inadequate breast milk removal can result in breast swelling or breast milk engorgement . Breast milk engorgement in postpartum mothers requires proper care and management. The researchers conducted this study at PMB Tjasini because many postpartum mothers experience breast milk engorgement at this facility. This study aimed to determine the effect of cabbage leaf compresses on breast milk engorgement at PMB (Independent Midwife Practice) Tjasini in 2025. Methods: This study used a pre-experimental design with a one-group pretest–posttest approach. The study population comprised 10 postpartum mothers in the PMB Tjasini area. The sample included 10 respondents selected using purposive sampling. Results: The univariate analysis showed that the mean breast pain score in postpartum mothers before receiving cabbage leaf compresses was 5.80, while after the intervention it decreased to 3.80. The bivariate analysis showed a significant effect of cabbage leaf compresses on breast pain in postpartum mothers in the PMB Tjasini area in 2025 (p-value = 0.000). Conclusion: Breast milk engorgement can be prevented by increasing support for postpartum mothers to initiate breastfeeding early.